A comparative account of coelomocyte of earthworm ecotypes with reference to its morphology, morphometry, density, phagocytosis, autofluorescence, and oxidative status. (27th May 2022) - Manna, Sumit; Ray, Abhishek; Gautam, Arunodaya; Mukherjee, Soumalya; Ray, Mitali; Ray, Sajal
Abstract: Earthworms inhabit different strata of moist soil. Epigeic and endogeic earthworms prefer superficial and inner stratum of soil respectively, whereas, semiaquatic species are distributed around hydrated soil near ponds and lakes. Coelomocytes, the chief immunoeffector cells of coelomic origin, perform diverse physiological functions like phagocytosis, maintenance of cellular homeostasis, and acid–base balance of coelomic fluid, graft rejection, elicitation of cytotoxic, and oxidative responses under the challenges of pathogens and toxins. The present study aims to analyze selected morphological and functional parameters in three differentially adapted Indian earthworms of nonsimilar habitats. Coelomocytes of Glyphidrilus tuberosus (Stephenson, 1916) (semiaquatic), Perionyx excavatus (Perrier, 1872) (epigeic), and Eutyphoeus orientalis (Beddard, 1883) (endogeic) were isolated for morphological and morphometric analyses and subjected to determination of phagocytic, oxidative, and cytotoxic responses. Activities of phenoloxidase, pro, and antioxidant enzymes, and autofluorescence were determined in the extruded coelomocytes of earthworms of three contrasting habitats. The differential result may be correlated with species‐specific responses and variation in habitat preference and related adaptation. Abstract : The difference in density, cytotoxicity, and oxidative status of coelomocytes of three species. Variation in autofluorescence, the phagocytic response of coelomocyte of three ecotypes. Nonsimilarity of results may be due to species specificity and related adaptation.